2016
DOI: 10.1177/0021998316630801
|View full text |Cite
|
Sign up to set email alerts
|

Efficient experimental characterisation of the permeability of fibrous textiles

Abstract: Two experimental set-ups used to characterise the in-plane and through-thickness permeabilities of reinforcing textiles have been developed and are presented. Both the experimental testing and data processing techniques used have been selected to ensure that the characterisation is completed in an efficient and robust method, increasing the repeatability of tests while minimising user induced errors as well as the time and resources needed. A number of key results and outputs obtained are presented from tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Endruweit [11] studied the effect of the yarn cross-sectional shape on the resin flow between inter-yarn gaps by combining theoretical analysis with numerical simulations. Endruweit [12] and Swiry [13] studied the permeability of single/multi-layer plain woven fabrics and investigated the influence of the number of layers on the permeability. Chen [14] used a dual-scale model to predict the fabric permeability, and the results showed that the permeabilities of fabrics with the same fiber volume fractions were not necessarily the same.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endruweit [11] studied the effect of the yarn cross-sectional shape on the resin flow between inter-yarn gaps by combining theoretical analysis with numerical simulations. Endruweit [12] and Swiry [13] studied the permeability of single/multi-layer plain woven fabrics and investigated the influence of the number of layers on the permeability. Chen [14] used a dual-scale model to predict the fabric permeability, and the results showed that the permeabilities of fabrics with the same fiber volume fractions were not necessarily the same.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the 2.5D woven preform was treated as a porous media. The principle in-plane permeability and the angle between the principal permeability and the weft of the fabric were measured at four different shear angles by the radial flow method [13]. A finite element model of the unit cell was established for the four different shear angles, to take into account the changes in yarn morphology caused by the shear deformation.…”
Section: Introductionmentioning
confidence: 99%
“…In this kind of method, measurements are made in a dry medium, i.e. at exact point that the fluid reaches the sensor [19].…”
Section: Introductionmentioning
confidence: 99%
“…Saturated methods are more commonly used in transverse permeability determination. A recent work presented in [19] proposes the use of an Instron 1186 Universal Testing Machine (UTM) to control the reinforced thickness. Once reinforced thickness can be changed with the UTM, different volume fractions can be set concurrently to the permeability test, making easy to perform in-depth study of the compactionpermeability relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Besides nesting, the transverse permeability of fabrics can also be affected by other factors, such as the deformation of fiber tows resulting from flow-induced compaction, [9,20,21] reinforcement distortions, [22,23] and dual-scale flow. [24][25][26][27][28] Affected by these factors and also the intrinsic features of different fabrics, such as the material and the woven pattern, the range of saturated transverse permeability can be very large, which generally varies from 10 −10 m 2 ( [14,18,[29][30][31] ), 10 −11 m 2 ( [12,13,19,32] ) to 10 −12 m 2 or even lower ( [9][10][11]20,33] ). No standard procedure has yet been proven to measure the saturated transverse permeability of fibrous reinforcements.…”
mentioning
confidence: 99%